DEATH ANXIETY IN CANCER PATIENTS IN PAKISTAN: THE MEDIATING ROLE OF RELIGION ORIENTATION AND THE MODERATING ROLE OF MEANING IN LIFE - Muhammad Awais-E-yazdan; Dr. Aqeel Ahmad Khan; Dr. Aftab Hussain; Bisma Akhlaq; Ahmed Ikram; Ammara Iqbal (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
The objective of this study was to examine the factors associated with death anxiety among cancer patients, namely self-esteem, social support, medical coping, and resilience, considering the mediating role of religious orientation and the moderating role of meaning in life. In the current study, 386 cancer patients voluntarily participated, of which 66% were male and 34% were female. The results of the regression analysis suggest that self-esteem, social support, medical coping mechanisms, and resilience exert a negative influence on death anxiety. Furthermore, a negative meaning in life moderates the relationship between self-esteem, social support, and medical coping, and death anxiety. However, in terms of the resilience scale, meaning in life does not demonstrate a statistically significant correlation with death anxiety. An external religious orientation significantly mediates the relationship between self-esteem and death anxiety, and between social support and death anxiety. Conversely, an internal religious orientation mediates negatively between self-esteem, social support, medical coping, resilience, and death anxiety.